COVID-19, indications for professional football teams and referees training resumption - Gavino Donadu, M.; Pizzi, A. R.; Zeppilli, P. (The Journal of Infection in Developing Countries, 2020)
These indications were drawn up by the Federal Medical-Scientific Commission (FIGC Commission), supplemented for the necessary time by some experts on the subject; currently they are intended to grant the highest achievable guarantee level to protect the health of players, referees and all professionals involved in case of resumption of collective training (Document dated 18 April 2020). They were designed to minimize the risk of contagion were thus based on the fact that during that phase of SARS-COV-2 virus pandemic (COVID-19) and in the absence of an effective vaccine, the zero-contagion risk did not exist and does not exist to date. Those guidelines have been updated on the basis of ongoing medical-scientific evidence, taking into account the indications given by the Technical-Scientific Committee and the opinion of the Italian Football Federation representatives, during a meeting that took place on May 7 and was transmitted to FIGC on May 11, 2020; these indications are to be considered stringent and binding for the purposes of sport training resumption.